Strategi Pemasaran Serbuk Jamu Instan UMKM Tiga Dara di Masa Pandemi Covid 19 - Susiana Purwantisari; Anindya Ardiansari; Siti Nur Jannah; Rizky Wahyu Saputro (Jurnal Surya Masyarakat, 2022)
Empowerment of Micro, Small and Medium Enterprises (MSME), requires model empowerment, which includes increasing existing MSME to be more advanced in order to be able to compete tightly in free market competition. Since ancient times, empon empon has been proven to have medicinal properties as herbal medicine, which is not only used as a medicine but also as a beauty treatment. One of the MSME that processes empon-empon into instant herbal medicine is Tiga Dara MSME which is located at Jalan Urip Sumoharjo No. 45 East Ungaran Subdistrict, Semarang Regency. Instant herbal powders produced by UD Tiga Dara include instant powders of Ginger, Turmeric, Temulawak, Mahkota Dewa, Kencur etc. The importance of maintaining body immunity during the COVID-19 pandemic is closely related to the availability of instant herbal powder products with empon-empon raw materials, especially ginger. During this pandemic, the demand for instant herbal medicine powder has increased, but Tiga Dara MSME still have limitations in the sales system. The method used in this community service is in the form of training and mentoring MSME in making web and social media as a means of marketing instant herbal powder products. This service aims to assist MSME in marketing their products in order to improve the economy of Tiga Dara MSME. With the existence of the Web and social media as one of the media for product marketing, it is hoped that it can increase sales from MSME and can improve the community's economy so that it can achieve community welfare.